Многоуровневая оптическая память на микро- и наноразмерных структурах - Demyohin, V. V.; Danilov, V. V. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
A method is proposed to increase the recording density of information in nanoscale storage media by extending to these media the concept of multilevel recording, previously developed for microstructural storage media. Another method is suggested to enhance the recording density of micro- and nanoscale media through the use of the three-dimensionality of each storage cell.